KOMUNIKASI ANTAR BUDAYA (STUDI KASUS : PERTUKARAN PELAJAR INDONESIA DI MALAYSIA) - Tarisa Febrina Maharani,; Desy Misnawati,; Bastian Jabir Pattara, (Juremi: Jurnal Riset Ekonomi, 2024)
Intercultural communication occurs during communication between individual or groups of different races, ethnicities, or socio-economic level. The differences between two or more cultures that meet each other can of course give rise to different patterns of intraction and communication, this is a resultof the diverse experiences, values and perspectives of each culture. This research was conducted to understand intercultural communication that course among Indonesian studens and how they overcome these communications barriers , as well as their efforts to interact with each other. This research uses qualitative methods. Data was collected using interview techniques with three Indonesian students studying at the state University of Malang. To achive this aim, five research questions were asked. The results of this research show that Indonesian intercultural communication is quite good, although initially there were many obstacles in the communication process, such as problems with diffrences in terms in the language used, habits, and the way of conveying information (both directly and via social media) which caused misunderstandings. However, this is not an obstacle for them to continue interacting and communicating with each other. To overcome this problem, they must learn more about Malaysian culture and respect each other’s cultural differences.